A Case of Type 2 Youssef’s Syndrome following Caesarean Section for Placenta Previa Totalis - Sefa Kurt; Funda Obuz (Case Reports in Obstetrics and Gynecology)
Vesicouterine fistula is a rare type of urogenital fistulas. It is most commonly observed after cesarean section (C/S) due to iatrogenic reasons. In this article, a case of a vesicouterine fistula which developed after C/S operation is presented. This was the patient’s second C/S and this time placenta previa totalis was the primary pathology. Since it is a rare complication, we found it interesting, and, in this article, this clinical problem was discussed with details about diagnosis and treatment in light of the literature.